Long Acting Reversible Contraception After Surgical Abortion With High Rate of Continuation and Patients' Satisfaction - Paola Algeri; Laura Imbruglia; Laura Colonna; Vanda Savoldi; Nunzia Mastrocola; Silvia von Wunster (Tehran University of Medical Sciences, 2024)
Objective: In Italy the percentage of repeated abortions is about 24%. Long-acting reversible contraceptive (LARC) methods are currently considered the most effective mode worldwide and are associated with the highest rate of 12-months continuation, with a potential reported reduction of recurrent abortions. The aim of this study was evaluating LARC continuation and the patients' satisfaction at two and twelve months in use. Materials and methods: A longitudinal observational study collected women who underwent surgical abortion and placed a LARC method at the time of abortion in our hospital. Results: Totally 828 women underwent surgical abortion during the study period from which 434 choose a LARC method. After two months the rate of continuation of 52mg LNG IUD was 100% in women presenting for follow-up. Continuation rate at one year was approximately 70% for all LARC methods. More than 70% of women declared themselves satisfied or very satisfied with all LARC methods. Conclusion: Despite a high rate of patient loss at follow-up, LARC methods showed a high rate of continuation at two and twelve months, with a high degree of patients' satisfaction.